The Influence of E-Service Quality, Convenience, and Trust on Online Purchase Decisions at Shopee Marketplace - Permana, Radifan Nugraha; Ratnasari, Ina (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
Digital marketing is a form of business or activity carried out by marketers, both companies and individuals, with the aim of marketing a product or brand, both goods and services, through the use of digital information technology, such as using electronic media, or using digital-based media. Internet. Currently trading is carried out using an online trading system, an easy and fast way to transact as well as a fast and easy marketing system. E-commerce is a process of buying and selling online or electronic devices that use the internet as a means of buying and selling goods. The Marketplace that is currently popular with many people is Shopee. In 2022 Shopee is the second e-commerce that has the most visitors with a total of 132.8 million visitors. This indicates that Shopee is able to compete ahead of the competition against its competitors which are the best Marketplaces. Shopee is also still popular and favored by customers because it is in the category of the most visitors and a large number of consumers intending to make buying and selling transactions. The factors that influence purchasing decisions at Shopee include e-service quality, convenience and trust. This research uses descriptive verification method. The sample obtained was 400 respondents who were Shopee users in Indonesia with a quantitative approach. The sampling technique used is purposive sampling. The analysis of this research is the analysis of the scale range, multiple linear regression analysis. Tests carried out validity test, reliability test, normality test, t-test, f-test, test the coefficient of determination. Based on the results of the research, it shows that e-service quality, convenience and trust have a partial effect on purchasing decisions at the shopee marketplace. As well as based on the results of the study it is also known that there is a fairly strong influence simultaneously on the variables e-service quality, convenience and trust in purchasing decisions at the shopee marketplace.